Moderating effects of teachers teaching experience on home learning associated with literacy skills among Chinese preschoolers - Yee, Chan Mei; Arshat, Zarinah (Canadian Center of Science and Education, 2016)
This study was designed to determine the influence of home learning on Chinese preschoolers’ literacy skills is likely to be moderated by the level of teacher’s teaching experience. There were 136 preschoolers aged ranged between three to six years old with their parents and teachers recruited in this study using a Multi-Stage Cluster sampling technique. The results of the Hierarchical Multiple Regression analysis indicate that teacher’s teaching experience has a significant moderating effect on the strengths of the relationship between home learning and preschoolers’ literacy skills. Further research is needed to investigate more deeply to identify whether these relationships are upheld over time and with diverse sample.